Theory and application of Agricultural Innovation Platforms for improved irrigation scheme management in Southern Africa - Rooyen, Andre F. van; Ramshaw, Peter; Moyo, Martin; Stirzaker, Richard; Bjornlund, Henning (Informa UK Limited, 2017)
Many small-scale irrigation systems are characterized by low yields and deteriorating infrastructure. Interventions often erroneously focus on increasing yields and rehabilitating infrastructure. Small-scale irrigation systems have many of the characteristics of complex socio-ecological systems, with many different actors and numerous interconnected subsystems. However, the limited interaction between the different subsystems and their agents prevents learning and the emergence of more beneficial outcomes. This article reports on using Agricultural Innovation Platforms to create an environment in which irrigation scheme actors can engage, experiment, learn and build adaptive capacity to increase market-related offtake and move out of poverty.